Mathematics reasoning and proving of students in generalizing the pattern - Moh, Zayyadi; Dian, Kurniati (International Journal of Engineering and Technology, 2018)
The purpose of this study was to identify students' reasoning in generalizing the patterns that proved by generalizing the structural generalizations with involve the mathematical structures and empirical generalizations that emphasize perceptions or evidence derived from the found regularities. The subjects in this research were the 7th semester students of Mathematics Education of University of Madura, Indonesia. The research steps in this research were (1) giving the reasoning tests to the research subjects, (2) analyzing the results of reasoning tests to identify reasoning and mathematical proofs, (3) conducting in-depth interviews as the triangulation method, and (4) summarizing the tendencies of reasoning and proof of student in generalize pattern. Based on the results and discussion can be obtained that in the process of reasoning and verification, students in identifying the same pattern with trial and error, so by using trial and error students find many ways to generalize the existing pattern. However, sometimes through the use of ways of trial and error students find the right pattern. Therefore, the student only identifies a reasonable pattern and does not identify mathematical patterns, then makes reasonable assumptions about finding a relationship but only hypothetical and needs to prove the allegations and only do a few stages of reasoning and not doing the stages of proof, giving no argument and not doing a validation of the evidence.Â Â